Enforcement Of Regent Regulation Number 12 Of 2022 On Violations Of Operating Times Of Goods Cars On Roads In Tangerang Regency - Fudianto, Mahfudz; Silalahi, Wilma (Universitas Muhammadiyah Sumatera Utara, 2025)
Regent Regulation Number 12 of 2022 concerning the Second Amendment to Regent Regulation Number 46 of 2018 concerning Restrictions on Freight Car Operating Hours on Road Sections in the Tangerang Regency Region (Perbup 12/2022), is a legal umbrella that is present in anticipating traffic violations related to the regulation and restriction of operational hours, especially for vehicles or trucks transporting soil excavation that go back and forth every day along the roads of Tangerang Regency. The main idea of the birth of Perbup 12/2022 as stipulated in Article 3 paragraph (1), is to strictly regulate the operational time of goods transportation vehicles, namely from 22:00 WIB to 05:00 WIB. The restrictions as intended in paragraph (1) are applied to road sections in the regional area and are excluded for toll road sections. It is clear that the presence of Perbup 12/2022 is solely aimed at ensuring the continuity and smooth flow of road traffic in the Tangerang Regency area, where every day the road is crowded with traffic for various public vehicles, both two-wheeled and four-wheeled. The concern that if there is no Regent Regulation, there will be traffic crowded on the meeting road between public vehicles and land excavation trucks, even the risk of traffic accidents often occurs outside the limited time as stipulated in Perbup 12/2022